Efficiency of Ethanolic Leaf Extract of Solanum torvum Sw. against Staphylococcus spp. from Dog Skin and the Owner Hands. - นายมอญ, ณัฐกาญจน์; จารุเดชา, ธิติชัย; สืบขำเพชร, อารยา (Journal of Mahanakorn Veterinary Medicine, 2019)
Solanum torvum Sw. is an alternative and traditional medicine plant which commonly found in Thailand. The aim of this study was to investigate the antibacterial activity of 95% ethanol crude extract of S. torvum SW. Leaves against pathogenic bacteria isolated from dog skin and owner hands (in vitro). The isolated bacteria were identified based on their biochemical characterization and determined their antibacterial activity of the extracts by using broth microdilution test in microtiter plate 96-well and subculturing into LB rich agar in order to explore the minimal inhibitory concentrations (MIC) and minimum bactericidal concentration (MBC), respectively. The bacterial characterization used in this experiment was specific to the Staphylococcus spp. which revealed Staphylococcus aureus, Staphylococcus epidermidis, Staphylococcus sciuri and Staphylococcus chromogenes in both of the sample sources. MIC and MBC were ranged between 3.91- 62.5 mg/ml and showed the greatest antibacterialactivity against Staphylococcus chromogenes. This study suggested that the extracts was promising for development in the treatment against pathogenic bacterial skin diseases in the future.